Consumer preferences for farmed and ecolabeled turbot: A North German perspective. Issue 3 (3rd July 2018) - Bronnmann, Julia; Hoffmann, Julia
ABSTRACT: This paper investigates the importance of different attributes, including farmed and wild caught, and non ecolabeled and ecolabeled, for turbot in the German market as well as consumers' willingness to pay for specific attributes. The empirical analysis is based upon discrete choice experiments with 485 participants from northern Germany. A mixed logit estimation reveals a strong positive effect of ecolabeled seafood and the results indicate that respondents are willing to pay more for wild-caught fish than farmed fish. The analysis provides more interesting results: Consumers' attitude toward frozen fish is quite negative despite the fact that this is the best-selling processed form on the German fish market. Furthermore, socioeconomic characteristics have limited influence on the purchase decision of respondents. Providing information to the consumers enhances the effect of the product attributes and the resulting probability of purchase.